Front Cover: Albumin Conjugates of Thiosemicarbazone and Imidazole‐2‐thione Prochelators: Iron Coordination and Antiproliferative Activity (ChemMedChem 18/2021). (16th September 2021) - Sung, Yu‐Shien; Wu, Wangbin; Ewbank, Megan A.; Utterback, Rachel D.; Marty, Michael T.; Tomat, Elisa
Abstract : The Front Cover shows the bioconjugation of an antiproliferative prochelator to serum albumin via formation of a disulfide bond with a reduced cysteine on the protein. The abundance of albumin in blood is represented by the red background featuring red blood cells. The disulfide‐masked prochelators of this class have antiproliferative activities at submicromolar levels in a panel of cancer cell lines. Cover design by Matthew W. Lluis. More information can be found in the Communication by Elisa Tomat et al. .